APLIKASI PUPUK KANDANG SAPI DAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAHE (Zingiber officinale Rosc.) DI MEDIA GAMBUT - YULIANA YULIANA; ELFI RAHMADANI; INDAH PERMANASARI (Jurnal Agroteknologi, 2015)
Research was conducted in march to june 2013 in the experimental farm of agriculture and animal Science faculty of the islamic university of sultan syarif Kasim Riau. The objektives of the research are 1.) to know the influence of chicken and cattle manures on plant grownt and yield of ginger 2.) and to find the best dosage of chicken and cattle manures for growth and yield of ginger.The experimental design was Randomized Complet Block Design Factorial RCBD with 2 factor 3 replications and analized by Duncan’s Multiple Range Test  DMRT. The first Factor was differents of manures (chicken and cattle) and the second factor is doses of manure ( 0, 5, 10, 15, 20, and 25 ton/ha). The data were collected for plant height, amount of plant, leaf width member of tillers/ plant and wet weight of rhizome.Results of the research showed that chicken manure increased plant height at 16 weeks and wet weight of rhizome. Wet weight of rhizome with chicken manure 28,18 % was higher than cattle manure the best dosages of chicken and cattle manures was 5 ton/ha and in word plant height at 16 weeks, number of hears/ plant, number of tillers / plants and height of rhizomes. Aplication of 5 ton/ha of manures in wood number of tillers/ plant and wet weight of rhizome by 96,71% and 163,15 % respectively.